Antimicrobial activities of the essential oils of five Salvia species from - Paknejadi, Mansoureh; Foroohi, Fatemeh; Yousefzadi, Morteza (Archives of Advances in Biosciences, 2012)
Essential oils are volatile, natural, complex compounds formed by aromatic plants as secondary metabolites. In nature, essential oils play an important role in protecting plants in form of antibacterials, antivirals, antifungals, insecticides properties and also against herbivores. They also may attract some insects to use them in dispersion of pollens and seeds, or repel undesirable others. Present study describes the results of our study on the chemical composition, and antimicrobial activity of the essential oils from aerial parts of aromatic plants which collected from province of Tehran. The aerial parts of plants were collected at full flowering stage. The essential oils were isolated by hydrodistillation and analyzed by combination of capillary GC and GC-MS. Also their antimicrobial activities were considered according to the disc diffusion method and MIC values. Finally, five plant species (Salvia sclarea, salvia multicaulis, salvia verticillata, salvia limbata, Salvia choloroleuca) which showed good significant antibacterial were presented. These five plants belong to labiates’ family. Among these proposed plants salvia multicaulis and Salvia sclarea showed good antibacterial activity.